Room-temperature visible electroluminescence from aluminum nitride thin film embedded with aluminum nanocrystals - Yang, Ming (2010)
In this brief, room-temperature visible electroluminescence (EL) from aluminum nitride (AlN) thin films containing aluminum nanocrystals (nc-Al) prepared by a radio-frequency magnetron sputtering technique is reported. The EL shows a broad spectrum peaked at 565 nm (2.19 eV) when a negative gate voltage is applied. A linear relationship between the EL and the current transport in the nc-Al/AlN thin film system is observed, and both the current transport and the EL intensity exhibit a power-law dependence on the gate voltage. These results are explained in terms of the formation of percolation networks of tunneling paths by the nc-Al arrays and the radiative recombination of the injected electrons and holes via the deep-level defects at the locations of nc-Al along the tunneling paths.